Logistical Factors Influencing Cold Ischemia Times in Deceased Donor Kidney Transplants. Issue 2 (February 2016) - Shrestha, Sussie; Bradbury, Lisa; Boal, Matthew; Blackmur, James P.; Watson, Christopher J. E.; Taylor, Craig J.; Forsythe, John L. R.; Johnson, Rachel; Marson, Lorna P.
Abstract : Background: Prolonged cold ischemia time (CIT) is associated with a significant risk of short- and long-term graft failure in deceased donor kidney transplants across the world. The aim of this prospective longitudinal study was to determine the importance of logistical factors on CIT. Method: Data on 1763 transplants were collected prospectively over 14 months from personnel in 16 transplant centers, 19 histocompatibility and immunogenetics laboratories, transport providers, and National Health Service Blood and Transplant. Results: The overall mean CIT was 13.8 hours, with significant center variation ( P < 0.0001). Factors that significantly reduced CIT were donation after circulatory death ( P = 0.03), shorter transport time ( P = 0.0002), use of virtual crossmatch (XM) ( P < 0.0001), and use of donor blood for pretransplant XM ( P < 0.0001). The CIT for transplants that went ahead with a virtual XM was 3 hours shorter than those requiring a pretransplant XM ( P < 0.0001). There was a mean delay of 3 hours in starting transplants despite organ, recipient, and pretransplant XM result being ready, suggesting that theater access contributes significantly to increased CIT. Discussion: This study identifies logistical factors relating to donor, transport, crossmatching, recipient, and theater that impact significantly on CIT in deceased donor renal transplantation, some of which are modifiable; attention should be focussed on addressing all of these.